Entrepreneurial effect of rural return migrants: Evidence from China - Bao, Anze; Pang, Gefeng; Zeng, Guoping (Frontiers in Psychology, 2022)
The entrepreneurial effect of rural return migrants is important for rural economic development. Using the data of the China Labour Force Dynamics Survey (CLDS thereafter) 2018 and China Household Finance Survey (CHFS thereafter) 2019, we analyse the entrepreneurial effects of return migrants upon their return to their hometowns. We find that the rural return migrants can promote entrepreneurship among residents. Land circulation, human capital, and physical capital are stimulating factors in promoting rural entrepreneurial activities of return migrants. We recommend that the government actively guide the rural return migrants to start businesses and provide security for entrepreneurial activities by upgrading various entrepreneurial elements.